A critical interpretive synthesis of anti-novel coronavirus drugs. (2nd June 2020) - Xiaoli, Ren; Yang, Bing
Abstract : Objective: To statistically analyse the development and research progress of clinical trials of novel coronavirus disease drugs, and to provide references for their clinical trials and treatment. Methods: The following keywords were searched for: 'COVID-19', 'Interferon-α', 'Lopinavir/Ritonavir', 'Ribavirin', 'Chloroquine Phosphate', 'Arbidol', 'SARS-CoV-2', 'Severe Acute Respiratory Syndrome'. The search was conducted on the Chinese Journal Full-text Database, Chinese Biomedical Literature Database, Cochrane library, PubMed, as well as the website of the China National Health Commission to extract and evaluate relevant data. Results: Most studies used western medicine or traditional Chinese medicine and antiviral treatment. The main antiviral drugs used were interferon-α, lopinavir/ritonavir, ribavirin, chloroquine phosphate and arbido. Conclusions: At present, there are no specific therapeutic drugs. The novel coronavirus can be effectively controlled by rational use of interferon-α, lopinavir/ritonavir, ribavirin, chloroquine phosphate and arbidol.